UPAYA MENINGKATKAN KEMAMPUAN MENERAPKAN PEMBELAJARAN TEMATIK MELALUI TEKNIK SUPERVISI INDIVIDUAL DI SD NEGERI 174568 SIMORANGKIR - KATARINA TAMPUBOLON (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve the ability of teachers to apply thematic learning through individual supervision techniques at SD Negeri 174568 Simorangkir Semester 2 of the 2019/2020 academic year. This type of research is school action research (PTS). The results of the reflection of the first cycle are the results of thematic learning in the first cycle an average of 42.83 (B) Teachers who get a C value of 2 people who get a B value of 3 people and who get an A value of 1 person. The implementation of learning activities through peer teaching showed an increase compared to the results of the initial conditions which averaged 37.16 (C) an increase of 13.23%, but there were still teachers who got enough marks for 2 people, so cycle II actions were needed. The results of the reflection of the second cycle are Based on the data, the thematic learning outcomes in the second cycle are an average of 63 (A) teachers who get a B value of 2 people and those who get an A value of 4 people. The implementation of learning activities through individual supervision activities further enhances the ability of teachers in implementing thematic learning. In Cycle II, it shows an increase compared to the results of cycle I (B) the increase is 32.01% and there are no teachers who get a C grade. So it is not necessary to carry out cycle III because it has been proven to increase the ability of teachers in implementing thematic learning. ABSTRAKPenelitian ini bertujuan untuk meningkatkan kemampuan guru dalam menerapkan pembelajaran tematik melalui teknik supervisi individual di SD Negeri 174568 Simorangkir Semester 2 tahun pelajaran 2019/2020. Jenis penelitian ini adalah penelitian tindakan sekolah (PTS). Hasil refleksi siklus I adalah Hasil pembelajaran tematik pada siklus I rata-rata 42,83 (B) Guru yang mendapatkan nilai C 2 orang yang mendapatkan nilai B 3 orang dan yang mendapatkan nilai A 1 orang. Kegiatan pelaksanaan pembelajaran melalui peer teaching menunjukkan meningkat dibanding hasil kondisi awal yang rata- ratanya 37,16 (C) peningkatannya 13,23% namun masih ada guru yang mendapat nilai cukup 2 orang maka perlu adanya tindakan siklus II. Hasil refleksi siklus II adalah Berdasarkan data, hasil pembelajaran tematik pada siklus II rata-rata 63 (A) Guru yang mendapatkan nilai B 2 orang dan yang mendapatkan nilai A 4 orang. Kegiatan pelaksanaan pembelajaran melalui kegiatan Supervisi individual lebih meningkatkan kemampuan guru dalam menerapkan pembelajaran tematik. Pada Siklus II ini menunjukkan meningkat dibanding hasil siklus I (B) peningkatannya 32,01% dan sudah tidak ada guru yang mendapatkan nilai C. maka tidak perlu dilaksanakan siklus III karena sudah terbukti peningkatan kemampuan guru dalam menerapkan pembelajaran tematiknya.